Pola Hubungan Pemerintahan Desa Dan Parlemen Desa Menuju Good Governance - Agus Bahrudin (Serat Acitya, 2015)
The dynamics of the relationship patterns of village government and village parliaments formed following the political policies and the regulations drawn up by the government. Based on a good governance perspective, the strategic efforts in establishing patterns of relationship and renewal of the organization of village government. First, the village government (along with the village chief and BPD) must be sensitive and apply the principles of accountability, transparency and responsiveness in governance, policy, finance and public services. Second, strengthen the capacity (capacity building) village government in managing policy, finance, rural development and public services .. Third empower BPD capacity as an agent of interest articulation, policy makers and government control to the village. Fourth, strengthen the participation of villagers in the village consultation meetings through MUSRENGBANG container village. Fifth, establishing a partnership between the village government, BPD and . Sixth,  Applying the "village build" and "Build a Village" which is integrated in the planning of Rural DevelopmentKeywords: Village Government, Parliament village, good governance